Pemetaan Sosial Desa Sindang Kecamatan Sindang Kabupaten Majalengka - Ratnawulan, Nunuy; Kania, Nia (EDUPEDIA Publisher, 2022)
The Sindang village development issue strategy is a problem related to the phenomenon or has not been resolved in the previous six years and has a long-term impact on the implementation of sustainable development, so it needs to be addressed gradually. The implementation method carried out in this service is a descriptive analysis method that explains an event according to the actual situation in the field, the results of interviews and approaches in Sindang Village, Sindang District, Majalengka Regency with documentary evidence. This research was conducted for 1 semester in 2019 in the KKN course. The activity was carried out in collaboration with the community of Sindang Village, Majalengka Regency with a positive response. They provide information related to villages ranging from education, religion, culture, creativity, tolerance and adequate health facilities to improve the quality of life of the community. From agricultural produce, farmers form a farmer group to create a joint business. The quality of the products produced also provides a positive value for the people of Sindang Village to do business and improve the regional economy. However, the obstacles in the marketing process are the lack of business partners and the absence of network facilities for digital marketing due to the limited ability to use electronic tools.